Efficacy of PARP inhibition in Pde6a mutant mouse models for retinitis pigmentosa depends on the quality and composition of individual human mutations - Jiao, K (Cell Death Discov, 2016)
Retinitis pigmentosa (RP), an inherited blinding disease, is caused by a variety of different mutations that affect retinal photoreceptor function and survival. So far there is neither effective treatment nor cure. We have previously shown that poly(ADP-ribose)polymerase (PARP) acts as a common and critical denominator of cell death in photoreceptors, qualifying it as a potential target for future therapeutic intervention. A significant fraction of RP-causing mutations affect the genes for the rod photoreceptor phosphodiesterase 6A (PDE6A) subunit, but it is not known whether they all engage the same death pathway. Analysing three homozygous point mutations (Pde6a R562W, D670G, and V685M) and one compound heterozygous Pde6a(V685M/R562W) mutation in mouse models that match human RP patients, we demonstrate excessive activation of PARP, which correlated in time with the progression of photoreceptor degeneration. The causal involvement of PARP activity in the neurodegenerative process was confirmed in organotypic retinal explant cultures treated with the PARP-selective inhibitor PJ34, using different treatment time-points and durations. Remarkably, the neuroprotective efficacy of PARP inhibition correlated inversely with the strength of the genetically induced insult, with the D670G mutant showing the best treatment effects. Our results highlight PARP as a target for neuroprotective interventions in RP caused by PDE6A mutations and are a first attempt towards personalized, genotype-matched therapy development for RP. In addition, for each of the different mutant situations, our work identifies windows of opportunity for an optimal treatment regimen for further in vivo experimentation and possibly clinical studies.